Training for the Management of Vietnamese Enterprises in the Industrial Revolution 4.0 - Hien, Vu Thi Minh; Hai, Hoang Van; Loan, Tran Kim (VNU JOURNAL OF ECONOMICS AND BUSINESS, 2021)
The Industrial Revolution 4.0 has created rapid changes in management, administration, and development in Vietnamese enterprises. Having been faced with enomous opportunities and challenges as they are nowadays, one of the fundemental factors decisive for an enterprise’s development is management capability. Perception change, talent attraction, and organizational culture development require technological knowledge and leadership skills. Therefore, this article studies how the Industrial Revolution 4.0 has impacted corporate governance and in what management needs to be trained urgently so as to meet the requirements of the Revolution.